Socio-economic viability of the Malaysian Hajj Management and Fund Board model for India - Quazi Syed Aon bin Hassan (IIUM Institute of Islamic Banking and Finance, 2014)
The Malaysian Hajj Management and Fund Board (Tabung Haji) has proven to be a very successful faith-based financial institution in last five decades. It has enormous amount of potential to resolve variety of socio-economic challenges of the Muslim society. In view of the above fact, this study is conducted to examine the socio-economic viability of Hajj Management and Fund Board Model for India. It tried to capture the socio-economic challenges of Indian Muslims along with the challenges related to their performance of Hajj. In addition, the socio-economic viability is explored through conducting interviews with five participants. The data were collected with both secondary as well as primary technique of data collection. Primary data were collected to answer the research questions while the secondary data was collected to build the theoretical base for the study. E-questionnaire method was used as a primary data collection tool in order to avoid the geographical, time and cost related challenges. On the other hand, government reports, government portals, articles and books were used for secondary data. Descriptive analysis was utilized in this study to gauge the financial inclusion status of the respondents along with the hajj services related challenges in India. Factor Analysis is used to find the underlying structure among the variables defining the perception towards establishment of Hajj Management and Fund Board Model. Then Multiple Regression Analysis was utilized to find the relationship between the variables such as perception towards Interest Free Institution, socio-economic sustainability and establishment of Hajj Management and Fund Board Model. Framework Analysis was employed to analyze the qualitative data. The result indicates that establishment of such institution in India will certainly create employment opportunities, easily mobilize savings due to its interest-free feature and provide an investment platform to the society which in turn positively affect the socio-economic status and desire of pilgrims. The huge Muslim population is another factor which could influence the success of such institution in India. As far as regulatory challenges are concern, it is found that Tabung Haji operates as a Non- Banking Financial Institution. This very nature of Tabung Haji makes this model legally viable for India because to introduce such institution regulators doesn't have to make amendments to the existing Banking Regulation Act. Non-Banking Financial Institutions in India operate under Companies Act with the approval of the Central Bank of India.